JNJ-64619178 radiosensitizes and suppresses fractionated ionizing radiation-induced neuroendocrine differentiation (NED) in prostate cancer - Pawar, Jogendra Singh; Al-Amin, Md. Yusuf; Hu, Chang-Deng (Frontiers in Oncology, 2023)
Graphical Abstract